A STUDY ON THE TREND AND GROWTH OF REGIONAL RURAL BANKS IN INDIA (International Journal of Food and Nutritional Sciences, 2026)
In India's rural and agricultural economy development, Regional Rural Banks held a significant position. The current presentation will concentrate on operational performance analysis of RRBs in India, considering factors such as deposits, capital, profits, and loans and advances. For this reason, the growth rate and trend analysis will be applied using these tools. For better development of India's banks and economy, the researcher suggested valuable advice.